ANALYSIS OF THE POSSIBILITIES OF USING CAD PRODUCTS - Заика, Александр (SWorldJournal, 2020)
Schemes of construction of solids at computer modeling in CAD were investigated. Solid modeling in CAD allows to automate and combine the fields of geometric modeling and computer graphics, which in turn facilitated the work of engineers. In the study of